ZIKIR FIDA DALAM PANDANGAN MASYARAKAT DESA SUMOROTO KECAMATAN KAUMAN KABUPATEN PONOROGO (KAJIAN LIVING HADIS) - Munawar, Ali Mahfuz (IAINU Kebumen Prodi IAT, 2022)
Before Islam came, Javanese people believed in sending prayers to the dead so that they would be safe until Nirvana and could rest in peace. After Islam came, this tradition of sending prayers was not immediately eliminated. However, it was given a pattern containing Islamic values ​​by Sunan Kalijaga. So that an acculturation was created between Islam and the culture of sending prayers which was given the name fida. Fida is an activity carried out by Javanese people after death. This activity includes reading the letter al-Ikhlas a thousand times or reading tahlil 70,000/71,000 times which is addressed to the deceased with the aim of avoiding the torment of hellfire and getting rewards. This study attempts to find out the views of the Sumoroto Village community, Kauman District, Ponorogo Regency about fida. (1) How is the practice of fida in the Sumoroto Village community? (2) How do the Sumoroto Village community relate the practice of fida to the text of the hadith. In this study, the author tried to use the observation method, interviews, and documentation as data to support this research. The data analysis used is descriptive qualitative with a phenomenological approach to religion and anthropology of religious symbols by examining the concept of religiosity in the symbols present in the ritual. The results of the study concluded, (1) The meaning of fida for the people of Sumoroto Village is divided into two, namely burdening good deeds and freeing from the torment of hellfire (2) The views of the community about fida are diverse, such as getting rewards and being guaranteed by Allah SWT to avoid hell, as well as the growth of togetherness, helping each other, friendship and giving alms to the environment.